Classroom Management of Teacher at SMP-IT AL-Fityan School Medan City - Echa Putri Khairani; Nasrul Syakur Chaniago (Universitas Muhammadiyah Enrekang, 2023)
The learning process is an important aspect of education because learning is the core of the educational process. The learning process will always take place in an activity at school, he explained, namely learning activities in class. These activities need to be created and developed into a vehicle for the success of an effective learning process. This means that separate management is needed to develop the activity, and the management in question is classroom management. As for the studies in this writing are: (1). To find out the teacher class management plans at SMP-IT AL-Fityan School Medan, (2). The ability to manage classes carried out by teachers at SMP-IT Al-Fityan School Medan, (3) What are the obstacles in managing classes. The conclusions from this study are as follows: (1) Classroom management by the teacher to achieve learning objectives must be planned in advance with clear and functional steps as teaching preparation materials; (2) The teacher must consider the characteristics and needs of students in managing the class, so that the learning method/media used is more appropriate; and (3) in classroom management, a teacher needs a variety of skills and teaching methods to meet students' needs so that learning conditions remain optimal.